Close Companions at Church, Health, and Health Care Use in Late Life - Krause, Neal (2010)
OBJECTIVES: To see whether there are age variations in the relationships between having a close companion friend at church, health, and outpatient physician visits. METHOD: The data come from two waves of interviews in a nationwide survey of older adults. These data are analyzed with ordinary least squares multiple regression analyses. RESULTS: The findings reveal that older people who have a close companion friend in the place where they worship are more likely to rate their health in a favorable way over time. However, these health-related benefits emerge only among the oldest-old study participants. The data results further indicate that having a close friend at church is associated with fewer outpatient physician visits over time, but once again, the results are observed only among the oldest-old. DISCUSSION: The results from this study provide preliminary insight into one way in which spiraling health care costs may eventually be curtailed.